Indicators and predictors modifiable by the nursing department during the preoperative period: A scoping review - Fernández Fernández, Eloísa; Fernández-Ordóñez, Eloísa; García-Gámez, Marina; Guerra-Marmolejo, Cristina; Iglesias-Parra, María Rosa; García-Agua-Soler, Nuria; González-Cano-Caballero, María (Wiley, 2022)
Aim and objectives The aim of this study is to identify preoperative indicators and/or predictors of complications or inefficiencies in the surgical process that can be modified within nursing practice. Background Due to rapid sociodemographic and technological change, the global demand for surgical attention is rising exponentially, requiring new strategies for optimisation and sustainability in perioperative care. Design We conduced the scoping review using the methodology recommended by the Joanna Briggs Institute supported with The PAGER framework and guided by the PRISMA-ScR Checklist. Methods Four databases (CINAHL, MEDLINE, SCOPUS and PUBMED) were examined to extract relevant published results for elective surgery on adult patients during the period 2011–2021. This process identified 609 records. Exclusion criteria were applied, and the sample was then evaluated with the Quality Assessment Tool for Studies with Diverse Designs (QATSDD), after which 15 studies remained. Results The following preoperative indicators and/or predictors were considered: (1) Anxiety; (2) Pain; (3) Health education, knowledge and training; (4) Satisfaction; (5) Management/organisation (including costs, resources used/available, organisational issues, hospital stay (preoperative), standardisation and protocolisation. Conclusion The identification of five indicators and/or predictors of complications or inefficiencies in the surgical process, which can be modified by nursing, allows the effective application of interventions in the preoperative phase, optimising care and improving health outcomes. Relevance to clinical practice The development and implementation of specific nursing skills in the preoperative phase are essential to optimise the surgical process.
Keywords: Indicadores; Cuidados preoperatorios; Delay; Indicators; Nursing; Preoperative period; Protocols; Total quality management in health care